Barriers to the Career Advancement of Women managers : A Review - Dr. Rita Latha D’couto (International Journal of Advanced Science and Technology, 2020)
Many research studies highlight the special contribution that women bring to organizations and their effectiveness as managerial leaders. However, their failure to reach the highest management positions has paved the way for considerable research and debate. Against this  background of the perceived suitability of women for top level managerial positions, together with the paradox of the relative lack of women in the most powerful positions in corporate organizations, many research studies have been undertaken on the barriers  women face to progress through the organizational hierarchy. Here, an attempt is made to present a summary of the research findings regarding the individual, interpersonal, organizational and societal factors inhibiting the advancement of women into the senior ranks of management